INSTITUTIONALIZATION OF POLITICAL PARTIES THROUGH ARRANGEMENT OF CANDIDATE LEGISLATIVE MEMBERS IN BANYUMAS REGENCY - Pratiwi, Oktafiani Catur; Nurprojo, Indaru Setyo (Jurnal Ilmu Komunikasi Acta Diurna, 2023)
This paper will explain the institutionalization of political parties through the policy of structuring the Gerindra Party legislative candidates in the 2019 legislative elections in Banyumas Regency. The Banyumas Regency Gerindra Party was chosen as the research locus with the consideration that the Gerindra Party's vote acquisition in the 2019 election was very significant as a newcomer party. The method used in this research is a case study with a purposive sampling technique. Data collected by documentation studies, interviews, and observations. Research informants included DPC Gerindra Party officials in Banyumas Regency and legislative candidates who failed or succeeded in the 2019 legislative elections. The data were analyzed interactively and validated through source triangulation. The results of this study, first; the arrangement of legislative candidates in the 2019 election was carried out by the Gerindra Party with a local wisdom approach as a strategy to avoid 'party elite bias' so that the candidates proposed were candidates with high electability and community support. Target cadres include women activists, cadres of NU, Muhammadiyah, Al Ersyad organizations, village heads and community leaders and are placed in the constituency where they live. With this strategy of structuring cadres based on local wisdom, the Gerindra Party can choose potential cadres who have the support of a stronger mass base. So that the Gerindra Party's seat acquisition can be stable to this day..